Probiótico e simbiótico em rações de origem animal e vegetal pra frangos de corte - Silva, Wagner Thiago Mozer da (2010)
The objective of this work was evaluate the effect of different levels of inclusion of inulin (chicory root extract) in diets containing ingredients of plant and animal on performance, carcass characteristics (cuts and abdominal fat) and the parameters blood, for broiler chickens 10-40 days old. 1056 chicks were used from one day old, housed on reused litter in a completely randomized design with eight treatments and six replicates of 22 birds each, which were arranged in a factorial 2 x 4, where the first factor was the use of two diets (plant and animal) and the second factor represented by four levels of inulin (0.00, 0.25, 0.50, 0.75%). The probiotic used was composed of Lactobacillus acidophillus, Bifidobacterium bifidum and Streptococcus faecium. The characteristics evaluated were weight gain, final weight, average feed intake, feed conversion, viability 1-40 days of age. At 21 and 35 days of age were measured blood parameters (calcium, phosphorus, uric acid and total protein). At 40 days was carried out the slaughter of birds to assess the yield of carcass, breast, drumstick, thigh, wing and abdominal fat percentage. Within the analysis of economic viability was calculated the cost of the experimental diets, the index of economic efficiency and cost index. In the initial phase and growth was not found significant results for the performance variables. In the total periods of 1-40 days of age for the variable feed no significant effect (P <0.05) for levels of inclusion. Carcass yield was influenced (P <0.05) by food type regardless of the levels of inclusion of inulin. For the cuts, only the thigh showed a significant difference (P <0.05) for the type of diet. Was observed in abdominal fat interaction (P <0.05) between type of diet (plant and animal) and the levels of inclusion of inulin. For the blood parameters for 21 days was significantly different (P <0.05) between levels of inulin inclusion for the variables P and total protein, and 35 was again a significant difference (P <0.05) for phosphorus . The other variables were not affected with the use of inulin. The use of 2.5 g / kg inulin provides better feed for broilers at 1-40 days old. Inclusion of inulin reduces abdominal fat independent mind the type of diet. The use of feed containing animal ingredients provides improved higher carcass yield and higher thigh yield. The use of inulin affected the phosphorus stock you live at 21 and 35 days old. The use of inulin in diets of broiler feed cost rises mind independent of the use of ingredients of animal or vegetable